Implicit differentiation / Aishah Mahat ...[et al.] - Mahat, Aishah; Muhamad Kamal Roszaman, Nur Hasya Irdina; Aliff Rahman, Nur Najiha Balqisha; Ainol Adnan, Vadhana Dania; Mohd Nopiah, Zulkifli (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
This e-book, “Implicit Differentiation” aimed to help students in Calculus subject. Targeted users for this e-book are students who take Calculus course in pre- university. Calculus is more than numbers and equations – it’s a way of thinking that unlocks the mysteries of the universe. This ebook is your gateway to exploring patterns, solving problems, and discovering the logic that shapes our world. Whether you’re new or experienced, Calculus is connected to everything. With clear examples, this ebook invites you to see Calculus not as a task, but as an adventure. Welcome to the world of Calculus – let’s explore !